The Language of Life: DNA and the Revolution in Personalised Medicine - Francis S Collins (Profile, 2010)
In this title, the former head of the Human Genome Project reveals how you can join the personalised medicine revolution. We are in the midst of a medical revolution: in just a few years, we will be able to have our complete DNA sequenced at an affordable cost. Analysing the content of our genomes will allow a powerful estimate of our future risks of illness - from cystic fibrosis and Huntington\\\'s disease, to cancer and diabetes - which will help us devise our own personalised blueprint of preventive medicine. This will have enormous implications on everything from our day-to-day choices like diet and exercise, to childbearing and health insurance - and it may even challenge what we thought we knew about our ethnic histories. Combining cutting-edge scientific research with practical advice, Francis Collins examines this remarkable phenomenon, which will transform healthcare worldwide. We now know that the language spoken by our DNA is the language of life itself, and in this important book Collins shows how reading that language will help save lives.